On the relation between landlord and tenant in Ireland - Greer, Samuel M. (Dublin Statistical Society, 1853)
In venturing to direct the attention of this Society, for a short time, to certain provisions of law which now regulate the relation between landlord and tenant in this country, I feel that I am dealing with a subject which some may consider hackneyed and ill-chosen. It is so important, however, to the agricultural classes of this country, that I am willing to run this risk, in order to discuss some branches of the subject which have not yet received an adequate share of public attention. Indeed it would be utterly impossible, in a single paper, to give even an outline of the question in all its bearings; and this is the less necessary, because certain great leading principles are now pretty generally admitted on both sides; and the points to which I refer lie more in the debatable ground, which has not yet been so accurately surveyed, or mapped out by statesmen or or economists. Without further preface, then, the proposition which I maintain is this:? That when there is no specific contract making a different provision, a tenant should be bound to deliver up his tenement at the end of his tenancy in as good condition merely as he received it in; and if beyond this he have added to its letting value, during his tenancy, by his own industry and capital, he should be allowed to possess a legal interest in that increased value so long as it shall subsist.
A paper read before the Dublin Statistical Society on Monday, April 18th, 1853
Keywords: Land tenure; Land reform; 314.15